Thyroid systems engineering : a primer in mathematical modeling of the hypothalamus-pituitary-thyroid axis - Goede, Simon Lucas; Leow, Melvin Khee-Shing (River Publishers series in biomedical engineering., 2018)
Targets an optimal treatment of people suffering from thyroid hormone disorders. The content is motivated by in-depth observations of such patients whose rich data supported the theoretical framework arising from formal mathematical reasoning, guided by the nature of thyroid physiology.